Zoropelecinus zigrasi, a pelecinid wasp in mid-Cretaceous amber from Myanmar (Hymenoptera: Pelecinidae) - Engel, Michael S.; Grimaldi, David A.; Ortega-Blanco, Jaime (Novitates Paleoentomologicae, 2013)
The proctotrupoid wasp family Pelecinidae (Proctotrupomorpha: Proctotrupoidea) is recorded in Early Cretaceous amber for the first time, previous amber inclusions being from the Late Cretaceous or Tertiary. Zoropelecinus zigrasi Engel & Grimaldi, new genus and species, is described and figured from an exquisitely preserved female in Albian-Cenomanian amber from Myanmar. The genus is similar to other fossil pelecinids of the genera Pelecinopteron Brues (Paleogene ambers of the Baltic and Siberia) and Henopelecinus Engel & Grimaldi (Turonian amber, New Jersey). Although two subfamilies have at times been recognized (or even as two families) the Iscopininae are clearly paraphyletic with respect to Pelecininae and therefore of no classificatory value and accordingly synonymized herein (new synonymy).